2022
DOI: 10.1002/qre.3142
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring profiles in multistage processes using the multivariate multiple regression model

Abstract: Most recent production processes comprise multiple stages, where the final quality of products is determined by the upstream effects of output quality at each stage. Moreover, the quality of each stage is characterized by a functional relationship, referred to as a profile, between input variables and output quality variables. Therefore, the effective profile monitoring of the multiple stages is crucial in maintaining and improving the final output quality. A multistage process is separated into a series of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Lately, Ahmadi et al 24 suggested a new control chart for multiple linear profiles monitoring by means of two robust estimate methods. Park and Lee 25 proposed both Phase I and Phase II study of profile monitoring in multistage processes based on the multivariate multiple regression profile. The aforementioned control charts for Phase I and/or Phase II study of the general linear profiles are briefly summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, Ahmadi et al 24 suggested a new control chart for multiple linear profiles monitoring by means of two robust estimate methods. Park and Lee 25 proposed both Phase I and Phase II study of profile monitoring in multistage processes based on the multivariate multiple regression profile. The aforementioned control charts for Phase I and/or Phase II study of the general linear profiles are briefly summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Phase I: Mahmoud and Woodall, 3 Mahmoud et al, 6 Mahmoud, 17 Kalaei et al 12 Phase II: Kang and Albin, 1 Zou et al, 4 Gupta et al, 5 Zou et al, 7 Zou et al, 16 Eyvazian et al, 18 Zou et al, 19 Xu et al, 8 Huwang et al, 20 Amiri et al, 9 Kazemzadeh et al, 10 Khedmati and Niaki, 11,21 Zhang et al, 22 Ghashghaei and Amiri, 23 Abbas et al, 13 Yeganeh et al, 14 Ahmadi et al 24 Both Phase I and Phase II: Kim et al, 2 Moheghi et al, 15 Park and Lee. 25 used to estimate this functional relationship and hence control charts are developed based on the functional relationship estimated to check whether the relationship is stable or not.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze a two-stage dependent process, EWMA and CUSUM charts are suggested by Nabeel et al [25] using logistic distribution. Park and Lee [26] considered each stage of a multistage process as a profile structure and suggested a multivariate multiple linear regression model implemented in each stage using the orthogonal design.…”
Section: Introductionmentioning
confidence: 99%